The relationship between active teaching and learning with graduate's entrepreneurial intention and interest - Md. Shariff, Anita; Nik Hasan, Nik Fakrul Hazri; Mohamad, Zaleha; Jusoff, Kamaruzaman (2010)
Entrepreneurship course at UiTM offers the students an educational experience based on active teaching and learning concept. The success of the course in improving the graduates' intention and interest towards entrepreneurship is being studied. This research attempted to identify the contents of Entrepreneurial course that emphasize active teaching and learning approaches and their relationships towards enhancing students' entrepreneurial intention and interest. Critical aspects of the course's six main contents are being tested. The course contents include business plan initial preparations, business plan developmental stage, business plan presentations, lectures and tutorial, learning materials, and examinations. Results of the pilot test conducted with twenty one respondents, show high validity and reliability of the questionnaire. Three course contents have strong correlations with entrepreneurial intention and interest; one course content has strong correlation with entrepreneurial interest only while the other two course contents show correlations with neither interest nor intention. All contents show strong correlations between interest and intentions. The findings could help in identifying the core element considered to have strong relationship towards developing entrepreneurial intention and interest among graduates. It is recommended that greater focus are given to these core contents particularly in fine-tuning the course syllabus and in allocating the necessary educational resources for entrepreneurial educations at higher learning institutions.